KMOBPSO-Based High Reliability Controller Placement Algorithm in SDN - Jingting Xu; Hua Qu; Jihong Zhao (Dianxin kexue)
N+1 redundancy backup model was applied to controller placement problem in SDN in order to solve single node failure problem and to improve system reliability with taking system cost and latency into consideration，and the problem was abstracted as a multi-objective optimization problem. Meanwhile，an algorithm called KMOBPSO was proposed to calculate the result of high-reliability controller placement in SDN merged with K-means clustering algorithm and genetic operators. Simulations show that the proposed algorithm who has high accuracy，uniform distribution and wide coverage of Pareto front，can significantly improve the reliability of controller placement in SDN.